Anti-Proliferative Activity of Althaea Officinalis Extracts on Iraqi Breast Cancer Cell Line AMJ13 (Iraqi Journal of Medical Sciences, 2021)
Background: Breast cancer has been the highest-ranked malignancy among the Iraqi population since 1986. Althaea officinalis is a perennial plant and native to Iraq and Asia, Europe and United States of America.Objective: To evaluate the cytotoxicity of Althaea officinalis extracts on AMJ13 breast cancer cell line.Methods: The cytotoxic activity of crude, flavonoids, and phytosterols extracts were tested by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Apoptosis assay was done by Acridine orange–Ethidium bromide dual staining method.Results: The cell line was exposed to serial concentrations of Doxorubicin and extracts from (3.125 to 100 µg/ml) in triplicate of each concentration for 72 hours exposure period. The Inhibitory concentration fifty (IC50) values for Doxorubicin, crude, flavonoids, and phytosterols were as follows: 19.52 µg/ml, 25.18 µg/ml, 39.54 µg/ml, and 47.88 µg/ml, respectively.Conclusion: Althaea officinalis extracts have a significant cytotoxic activity and have the ability to cause apoptosis on AMJ13 breast cancer cells. Crude extract have the highest significant cytotoxic activityKeywords: Breast cancer, AMJ13 cell line, Althaea officinalis, cytotoxicity assay, apoptosis assayCitation: Kadhum HH, Abd AH, Al-Shammari AM. Anti-Proliferative activity of Althaea Officinalis extracts on Iraqi breast cancer cell line AMJ13. Iraqi JMS. 2021; 19(2): 163-171. doi: 10.22578/IJMS.19.2.5